Case Report: Exaggerated estradiol secretion in an infant with hypothalamic hamartoma - Vinkovic, Maja; Braovac, Duje; Dumic Kubat, Katja; Jovanovic, Ivan; Banovic, Maja; Krnic, Nevena (Frontiers in Endocrinology, 2025)
ObjectivesHypothalamic hamartoma (HH) is an important cause of central precocious puberty (CPP) in young children but is rarely described in infants. Interpretation of laboratory data could be difficult because gonadotropins and estradiol levels often overlap in healthy infants with mini-puberty and children with HH. Extremely elevated estradiol levels are mostly described in girls with peripheral precocious puberty.Case presentationWe present a 5.5-month-old girl with vaginal bleeding, significantly elevated estradiol levels (up to 3,974 pmol/L), elevated gonadotropins, and right ovarian cyst. Laboratory and radiologic evaluation revealed the HH as a cause of CPP. Immediately after the start of treatment with depot gonadotropin-releasing hormone analogue, age-appropriate undetectable levels of estradiol were achieved, with ovarian cyst regression and cessation of pubertal changes.ConclusionIf observed in the period of mini-puberty, high levels of estradiol accompanied by unsuppressed gonadotropins can complicate the discrimination between central and peripheral precocious puberty. This challenge emerges particularly due to the absence of the negative feedback mechanism in children with HH. This is the first report identifying extremely high estradiol levels as part of the phenotypic spectrum of HH in infants.